Regionally owned funds : mechanisms for delivery of EU Aid for Trade in ACP regions - Braun-Munzinger, Corinna (ECDPM MaastrichtNL, 2009)
Considers the establishment of regional funds in the ACP in the context of EPA negotiations. Outlines some key issues to be addressed during the process of establishing such funds. Provides a brief overview of the current state of play in implementing them in each ACP region.